Efektivitas Serbuk Daun Binahong (Anredera Cordifolia (Ten.) Steenis) terhadap Telur Cacing Haemonchus Sp pada Domba - Arja, Maulidani; Hanafi, Nevy Diana (Jurnal Ilmiah Universitas Batanghari Jambi, 2024)
Worm parasitic diseases are a serious problem in livestock, especially ruminants. This study aims to determine the anthelmintic effectiveness and concentration of Binahong leaf powder (Anredera cordiofolia (Ten.) steenis) on the mortality of Haemonchus sp worm eggs in sheep. This research is an experimental method with a completely randomized design with 1 factor, namely Binahong leaf powder dissolved in water at concentrations of 0 mg/kg, 200 mg/kg, and 250 mg/kg (three concentrations) which will be repeated six times. Observations were made before and after treatment for fourteen days given Binahong leaf powder. Then count the number of dead worm eggs in the feces through a microscope. The data that was obtained was then calculated and analyzed using Anova (Analysis of Variance) with table F using a Completely Randomized Design (CRD) pattern, then continued with the Duncan Test to find out which treatment had the most influence on the death of Haemonchus sp worm eggs. The results of the research showed that various concentrations of Binahong leaf powder as an anthelmintic were able to kill Haemonchus sp worm eggs in sheep feces positively and significantly with a concentration of 250 mg/kg being the concentration that had the highest mortality effect. The active compound content in binahong leaf powder is effective in killing 50% (LC50) of Haemanchus sp worm eggs at a dose of 194.55 mg/kg with a percentage of up to 100%.